Evaluasi Pertumbuhan Bibit Aren (Arenga pinnata (Wurmb) Merr.) Terhadap Pemupukan P dan Inokulasi Fungi Mikoriza Arbuskula - Maria Paulina; Irdika Mansur; Ahmad Junaedi (Rawa Sains: Jurnal Sains STIPER Amuntai, 2020)
Aren is one type of plant that has the potential to be developed because all parts of the plant can be used. Currently, the cultivation of sugar palm is still traditional and far less than other types of Arecaceae family. The research was conducted from August to October 2016 at the nursery site, and analysis of spore types and AMF colonization in the SEAMEO BIOTROP Bogor Silviculture Laboratory. This research was conducted on palm seedlings that were 19 months old. This study used a completely randomized design with 2 factors, namely P fertilization and AMF inoculation. The P fertilization factor has 2 levels, namely without P fertilization and given P fertilization. The inoculation factor for AMF consisted of 3 levels, namely without AMF inoculation, indigenous AMF, and my cover AMF. The results showed that P fertilization treatment and AMF inoculation did not significantly affect all observed variables, namely plants, number of leaf midribs, length of rachis, plant diameter, SPAD value, number of spores, and root colonization. There was 3 genus of spores, namely Acaulospora sp., Gigaspora sp., and Glomus sp., as well as 2 types of root infections in the form of hyphae and vesicles.